Right ventricular function in coronary slow flow: A two-dimensional speckle-tracking echocardiographic study - Ali Hosseinsabet; Shima Yarmohamadi; Sima Narimani; Nazanin Amini-farshidmehr (KARE Publishing, 2016)
Objective: Coronary slow-flow phenomenon (CSFP) is described as protracted passage of angiographic contrast agent to the distal portion of the epicardial coronary arteries in the absence of stenosis. Few studies have addressed the effects of this condition on right ventricular (RV) dysfunction. The present objective was to assess RV function in CSFP via 2-dimensional speckle-tracking echocardiography (2DSTE). Methods: A total of 29 patients with CSFP and 29 participants with normal coronary flow were compared regarding RV systolic and diastolic functions. Participants were matched for age, sex, hypertension, and diabetes mellitus. RV systolic and diastolic functions were evaluated with pulsed-wave tissue Doppler echocardiography and 2DSTE. Results: There were no statistically significant differences between the CSFP group and the control group regarding tissue Doppler echocardiographic and 2DSTE-derived indices. Conclusion: CSFP was not associated with tissue Doppler echocardiographic and 2DSTE-derived indices of RV systolic and diastolic function.